2016
DOI: 10.3171/2015.1.jns141577
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of serum microRNA-205 as a potential diagnostic and prognostic biomarker for human glioma

Abstract: G lioma is the most common primary intracranial tumor in adults, accounting for more than 40% of primary CNS neoplasms. In accordance with WHO classification, which is based on histomorphological criteria, gliomas are categorized as well-differentiated low-grade astrocytoma (WHO Grade I or II), anaplastic astrocytoma (WHO Grade III), or glioblastoma (GBM; WHO Grade IV). 15 The most frequent and malignant glioabbreviatioNs GBM = glioblastoma; KPS = Karnofsky Performance Scale; miR-205 = microRNA 205; miRNA = mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 25 publications
1
71
0
1
Order By: Relevance
“…A number of studies have investigated the potential role of circulating miRNAs in glioma survival and clinical outcomes [24, 25, 27, 29, 30]. For example, Zhi et al reported that up regulation of serum miR-20a-5p, miR-106a-5p, and miR-181b-5p was associated with advanced clinical stages of astrocytoma, and high expression of serum miR-19a-3p, miR-106a-5p, and miR-181b-5p was significantly associated with poor patient survival among astrocytoma patients [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated the potential role of circulating miRNAs in glioma survival and clinical outcomes [24, 25, 27, 29, 30]. For example, Zhi et al reported that up regulation of serum miR-20a-5p, miR-106a-5p, and miR-181b-5p was associated with advanced clinical stages of astrocytoma, and high expression of serum miR-19a-3p, miR-106a-5p, and miR-181b-5p was significantly associated with poor patient survival among astrocytoma patients [29].…”
Section: Resultsmentioning
confidence: 99%
“…Profiling of miRNAs circulating in serum or plasma may be particularly useful in glioblastoma patients, given the risks of sequential surgery and biopsy, and the lack of readily usable biomarkers to predict clinical outcome. Previous attempts have been made to assess circulating miRNAs in relation to glioblastoma prognosis [2430]. However, due to small sample size and a heterogeneous patient population, prognostic impact could not be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Так, уровни циркулирующих miR-128, -205 и -451a были ниже в сыворотке крови больных глиомами по сравнению с контролем или пациентами с менингиомой [120][121][122]. Анализ с использованием микрочипов и qPCR, ROC-кривых показал, что одновременное определение уровня экспрессии miR-15b и miR-21 в сыворотке крови помогает дифференцировать пациентов с глиомами от больных с другими поражениями головного мозга (метастазами и др.)…”
Section: микро-рнк как прогностические маркерыunclassified
“…In a study of 64 glioma patients, serum miR‐205 levels displayed a stepwise decrease with ascending tumor grade and additionally increased following surgery and decreased again during tumor recurrence. Further, patients with advanced pathological grade demonstrated longer overall survival times when serum miR‐205 levels were elevated 101, 102. Thus, serum miRNAs could serve as critical indicators of disease progression and outcome.…”
Section: Introductionmentioning
confidence: 99%